Chemotherapeutics challenges in developing effective treatments for the endemic malarias - Baird, J (2012)
The endemic malarias threaten the several billion people residing where transmission occurs. Chemotherapeutic strategy pitted against these threats hinges upon species- and stage-specific treatments guided by diagnosis and screening against sometime dangerous contraindications. This approach suits malaria as it occurs among travelers in the developed, non-endemic world. However, limiting treatment to that which diagnosis affirms may not be rational in endemic zones. Most of the endemic malarias remain out of diagnostic reach, either by inaccessibility of the parasite stage, insensitivity of the technology, or unavailability of diagnostic services. The partial and fragmented chemotherapeutic attack of malaria guided by confirmed diagnostics leaves most of the endemic malarias unchallenged. Development of elimination therapy, a single course of treatment aimed at all species and stages, would significantly advance progress against the major killers known collectively as malaria. © 2012.